2014
DOI: 10.1016/j.jbiomech.2014.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction and fibrosis

Abstract: Scarring and tissue fibrosis represent a significant source of morbidity in the United States. Despite considerable research focused on elucidating the mechanisms underlying cutaneous scar formation, effective clinical therapies are still in the early stages of development. A thorough understanding of the various signaling pathways involved is essential to formulate strategies to combat fibrosis and scarring. While initial efforts focused primarily on the biochemical mechanisms involved in scar formation, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
150
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(153 citation statements)
references
References 154 publications
(181 reference statements)
1
150
0
2
Order By: Relevance
“…This reciprocal feedback between tissue mechanics and cellular mechanosignaling circuits, referred to as mechanoreciprocity, is fundamental to development, to maintaining tissue homeostasis and to resolving wound healing (Duscher et al, 2014;DuFort et al, 2011). Owing to the elastic nature of the brain and its confinement in the skull, small changes in ECM properties or extracellular fluid pressure in disease states can lead to marked tissue stiffening and compression, resulting in a corruption of the fine-tuned mechano-circuitry.…”
Section: Mechanotransductionmentioning
confidence: 99%
“…This reciprocal feedback between tissue mechanics and cellular mechanosignaling circuits, referred to as mechanoreciprocity, is fundamental to development, to maintaining tissue homeostasis and to resolving wound healing (Duscher et al, 2014;DuFort et al, 2011). Owing to the elastic nature of the brain and its confinement in the skull, small changes in ECM properties or extracellular fluid pressure in disease states can lead to marked tissue stiffening and compression, resulting in a corruption of the fine-tuned mechano-circuitry.…”
Section: Mechanotransductionmentioning
confidence: 99%
“…The current study also found that the difference in volumetric change between SZ chondrocytes and their PCM increased with the initial aspect ratio, indicating that PCM proteins connecting to a flat chondrocyte in the SZ are stretched more than PCM proteins connecting to a spherical chondrocyte. These results suggest that the shape of the chondrocyte, especially in the SZ, can affect the mechanical microenvironment of the chondrocyte, leading to alternations of biological functions which are critical for extracellular mechanotransduction [47]. …”
Section: Discussionmentioning
confidence: 99%
“…The high stress microenvironment in the SZ may activate stress-sensitive ion channels at the chondrocyte membrane to modify specific mechanotransduction and biological functions. The tensile stresses and increased volume of the DZ chondrocyte may activate stretch-activated ion channels, which are key factors in the regulation of cytoskeletal function and intracellular mechanotransduction [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Scaffold pore size, morphology, and interconnectivity [52, 53] as well as the scaffold degradation rate [1, 54] can potentially reduce scar formation; however, the effects of substrate modulus on matrix deposition and alignment, angiogenesis, and macrophage phenotype have been less extensively investigated. Mechanical stress can have beneficial effects on cutaneous regeneration via enhanced proliferation, angiogenesis, and stem cell recruitment [55], but it also increases infiltration of inflammatory cells and decreases apoptosis of local cells involved in wound remodeling, both of which are major factors in tissue fibrosis and scarring [56]. These competing effects suggest that there may be an optimal substrate modulus that promotes the regenerative versus the scarring phenotype.…”
Section: Discussionmentioning
confidence: 99%